Training of core trainers on CPG management of asthma in adults (second edition) 2025 - Md-Yasin, Mazapuspavina; Musa, Aisya Natasya (Faculty of Medicine, 2025)
Asthma care in Malaysia took a major step forward on 25 May 2025 with the launch of the Second Edition of the Clinical Practice Guidelines (CPG) on Asthma Management in Adults. The launch, held at the 2nd Malaysia National Asthma & COPD Preceptorship Conference (MNACPC) in Kuala Lumpur, was officiated by YBhg. Dato’ Dr. Mohd Azman Yacob, Director of he Medical Development Division, Ministry of Health Malaysia.Behind this milestone was a dedicated multidisciplinary team of 16 experts, chaired by Associate Professor Dr. Andrea Ban Yu-Lin, respiratory physician at Universiti Kebangsaan Malaysia. The team also included members from the Faculty of Medicine, Universiti Teknologi MARA (UiTM), Dr. Aisya Natasya Musa, Respiratory Physician, and Dr. Mazapuspavina Md. Yasin, Family Medicine Consultant.